Relative competency of urea in augmenting physiological and agronomic traits of baby corn (Zea mays) - SHARMA, ARPITA; CHOPRA, N K; CHOPRA, NISHA K; KUMAR, ASHWANI; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2020)
Nitrogen is indispensable for aggrandizing productivity of crop but the losses associated due to swift transformation and release pattern are subjected to various losses leading to pitiful amount left for crop uptake, pollution and resource wastage. Present study was conducted to evaluate the efficacy of coated urea and nitrogen rates on baby corn growth, yield and NUE. The experiment comprised varieties PHM-1 and HM-4, coated urea (NCU, ZCU, SCU and PU) and nitrogen levels @180, 150, 120 kg N/ha along with the control. The study revealed that PHM-1 obtained significantly higher plant height, no. of cobs and weight of dehusked cob that led to significant increase of 18.47 and 19.67 % higher husked and dehusked cob yields over HM-4 which attained 12.6% higher fodder yield over latter. The baby corn cob yield and fodder yield were significantly higher in coated urea over prilled urea. The husked and dehusked yield of baby corn was higher in neem-coated urea over prilled urea by 14.81 and 14.37% respectively. H o w e v e r , a reduction of 59.9% in total fodder yield was recorded in control when compared to 180 kg N ha. Also, NPK uptake was higher then PHM-1 and uptake by coated urea was higher then prilled urea along with high uptake for 180 kg N/ha, further the AE and higher PE of baby corn cob was found highest in variety PHM-1 although for fodder, the higher AE was recorded in HM-4, whereas ANR was higher in PHM-1.